A new generation needle- and adjuvant-free trivalent plague vaccine utilizing adenovirus-5 nanoparticle platform - Paul B. Kilgore (Nature Portfolio, 2021)
Abstract A plague vaccine with a fusion cassette of YscF, F1, and LcrV encoding genes in an adenovirus-5 vector (rAd5-YFV) is evaluated for efficacy and immune responses in mice. Two doses of the vaccine provides 100% protection when administered intranasally against challenge with Yersinia pestis CO92 or its isogenic F1 mutant in short- or long- term immunization in pneumonic/bubonic plague models. The corresponding protection rates drop in rAd5-LcrV monovalent vaccinated mice in plague models. The rAd5-YFV vaccine induces superior humoral, mucosal and cell-mediated immunity, with clearance of the pathogen. Immunization of mice with rAd5-YFV followed by CO92 infection dampens proinflammatory cytokines and neutrophil chemoattractant production, while increasing Th1- and Th2-cytokine responses as well as macrophage/monocyte chemo-attractants when compared to the challenge control animals. This is a first study showing complete protection of mice from pneumonic/bubonic plague with a viral vector-based vaccine without the use of needles and the adjuvant.